Persepsi Masyarakat terhadap Kinerja Pegawai Kantor Kecamatan Pineleng Kabupaten Minahasa - Toman Hutapea (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Public perceptions of the performance of the employees of the Pineleng Sub-District Office in the City of Minahasa were positive efforts from the people in Pineleng's sub-district to improve the services of the apartement of the Pineleng District Office. This study aims to (1) Describe the public perception of the quality of service in the office of the Pineleng District of Minahasa City in carrying out tasks in serving the community. The research method used is a qualitative research method. The results of this study stated that public perception of the organizational performance of the Pineleng Sub-District Office in Minahasa City for leadership was appreciated both because of the discipline shown by the leadership in the office. In the quality of service to the community is not optimal because: (1) Often found employees leave the place during service hours, (2) Employees are not quick to respond to the needs and suggestions given by the community.